Diatoms Green Nanotechnology for Biosilica-Based Drug Delivery Systems - Monica Terracciano; Luca De Stefano; Ilaria Rea (MDPI AG, 2018)
Diatom microalgae are the most outstanding natural source of porous silica. The diatom cell is enclosed in a three-dimensional (3-D) ordered nanopatterned silica cell wall, called frustule. The unique properties of the diatom frustule, including high specific surface area, thermal stability, biocompatibility, and tailorable surface chemistry, make diatoms really promising for biomedical applications. Moreover, they are easy to cultivate in an artificial environment and there is a large availability of diatom frustules as fossil material (diatomite) in several areas of the world. For all these reasons, diatoms are an intriguing alternative to synthetic materials for the development of low-cost drug delivery systems. This review article focuses on the possible use of diatom-derived silica as drug carrier systems. The functionalization strategies of diatom micro/nanoparticles for improving their biophysical properties, such as cellular internalization and drug loading/release kinetics, are described. In addition, the realization of hybrid diatom-based devices with advanced properties for theranostics and targeted or augmented drug delivery applications is also discussed.